A Gasoline Fuelled Pre-Chamber Ignition System for Homogeneous Lean Combustion Processes - Schumacher, Moritz; Wensing, Michael (SAE Technical Papers, 2016)
Pre-chamber ignition systems enable the combustion of homogeneous lean mixtures in internal combustion engines with significantly increased thermal efficiency. Such ignition systems provide a much higher ignition energy compared to a common spark ignition by burning a small portion of the charge in a separate chamber, generating multiple ignition sites in the main combustion chamber and increasing the turbulent flame speed. Pre-chamber ignition systems are commonly used in large natural gas engines but the integration in automotive engines is not feasible so far due to the lack of suitable fuelling systems needed to keep the pre-chamber mixture stoichiometric at lean operation of the engine. Based on preliminary investigations we developed an ignition system with fuelled pre-chamber for automotive engines utilizing the available space for the conventional spark plug. These investigations proved the thermal stability and function of the system up to a specific power of 100 kW/l and a speed of 12500 rpm. The fuelling system saturates air with fuel vapour and injects this mixture time-controlled into the pre-chamber. The already available fuel tank ventilation system in Otto-engine powered cars can provide such an air-gasoline-vapour mixture. Further, the system uses an inexpensive low pressure solenoid valve to control the pre-chamber enrichment. The prototype of the pre-chamber incorporates a spark plug, fuelling valve, thermocouple and pressure transducer and was measured in a full engine at characteristic operating points regarding thermal efficiency, combustion process and emissions. The ignition system showed the ability to ignite highly diluted mixtures with = 1.6 and an efficiency gain of 14.8% compared to stoichiometric spark plug operation at 4.5 bar IMEP and 1500 rpm with a NOx emission below 100 ppm.
Created from Fastlane, Scopus look-up